DESIGN OF BUCKLING-RESTRAINED BRACED FRAMES WITH DYNAMIC-LINEAR ANALYSIS AND STATIC-NONLINEAR ANALYSIS PEMALANG GREAT MOSQUE - Galvindy, Gelasius
Indonesia is a country with largest Muslim people in the world, that is around 222 millions people or more than 87% people of Indonesia. In accordance with that, the development of mosque is very important as it serves as a place for Muslim people to pray. Kec. Pemalang which is located in Kab. Pemalang, is one of the people activity centre that includes shopping district, public park, and Pemalang Great Mosque. Current mosque with area of 2500 squared meters seems to be not enough for Pemalang people, and expansion of the mosque is desired. Structural planning starts with the design of roof structure. Using steel as construction material, roof will be designed as ordinary moment frame (OMF). Roof structure will not be designed to plastified during seismic loading and will be connected to main structure with pinned connection. Roof will be designed based on roof loading with polytetrafluoroethylene membrane, self-weight of structure element, and wind load. Reaction force resulted by the loading will be then transferred to main structure. Mosque main structure is planned to be a refugee place following large earthquake. Based on that, main structure will be designed with importance factor equal to 1,5. Using steel as construction material, structure will be designed as buckling-restrained bracing frame (BRBF). This system is selected based on some considerations such as when plastified during seismic loading, bracing element may be replaced that the whole structure need not to undergo whole renovation. Besides that, BRBF will also result in smaller structure drift and thus will protect the content of building that is usually broken due to building drift. Before the planning of main structure, stairs will be modelled and designed first. Stairs is modelled separately from the main structure as it will ruin the mode shape of the structure. After that, stairs reaction due to each kind of loading will be applied to main structure. Besides that, structure will also use metal deck as a floor loading. The selection of concrete topping thickness will be based on deflection requirement on national standard and fire rating duration. After that, metal deck property will be designed as a part of main structure. The main concept of buckling-restrained braced frame is plastic mechanism analysis, that is a mechanism where the beam and column in the BRB frame may not yield before the yield of the bracing. Therefore, beam and column in the BRB frame will be designed based on maximum capacity of the bracing. Maximum capacity of bracing depends on the size of the bracing that is determined based only on axial internal force on the bracing due to seismic loading. This will be an iterative process as the change of bracing size will change the structure weight and behaviour, and also the selection of the beam and column to achieve the optimum design. For the bay that is designed to resist only the gravity loading, members dimension will be selected based on the capability to develop internal force due to the loading. After that, dynamic-linear analysis using spectral response analysis will be performed. Analysis will include eccentricity, drift, p-delta effect, horizontal irregularities, vertical irregularities, and redundancy check. It is obtained that the structure designed fulfill the analysis requirement. To ensure that the building will be able to be used as a refugee place following large earthquake, the design will be checked based on its performance using static-nonlinear analysis, that is pushover analysis. It is obtained that the whole structure falls into the category of life safety and thus it can be used following large earthquakes and the structure is not too extravagant. Next, basement analysis and design will be performed. Basement design starts with the selection of sectional dimension based on loading from main structure, park and soil loading, and other super-imposed loading. Static-linear analysis using equivalent lateral force procedure will be performed to obtain structure irregularities, etc. Two-stage analysis will also be performed to ensure that the basement is much stiffer than the main structure. Because the basement area is much bigger than the main structure, two-stage analysis requirement is easily fulfilled. After that, each component of the structure will be detailed.